1968
DOI: 10.1073/pnas.59.4.1294
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of infectious bacteriophage fd DNA's and an assay for in vitro host-controlled restriction and modification.

Abstract: Arber2 has shown that bacteriophage fd, which contains single-stranded circular DNA (Marvin and Schaller12) is restricted by E. coli B and E. coli (P1) +. This report presents detailed data on the restriction of both the infectious, singlestranded fd-phage DNA and the infectious, double-stranded fd-replicative form (RF)18 DNA. It also describes an infectivity assay for in vitro host-controlled restriction and modification. This assay has been used to find restriction enzymes in fractionated extracts of E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1969
1969
1997
1997

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Particular physiological conditions of cells may ca'use weakness in restriction of phages (Bertani & Weigle, I953; Uetake, Toyama & Hagiwara, 1964;Holloway, 1965;Rolfe & Holloway, 1968) and Luria & Human (1952) encountered this condition with the use of stationary phase cells. Benzinger (1968) explains the weaker restriction of phage fd infectious DNA by spheroplasts compared to that of intact fd phage in cells ofE. coli as due to the greater age of spheroplasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular physiological conditions of cells may ca'use weakness in restriction of phages (Bertani & Weigle, I953; Uetake, Toyama & Hagiwara, 1964;Holloway, 1965;Rolfe & Holloway, 1968) and Luria & Human (1952) encountered this condition with the use of stationary phase cells. Benzinger (1968) explains the weaker restriction of phage fd infectious DNA by spheroplasts compared to that of intact fd phage in cells ofE. coli as due to the greater age of spheroplasts.…”
Section: Discussionmentioning
confidence: 99%
“…Takano et al (I968) found the restricting enzyme of fi-R factors in Escheriehia coli K 12 for phage A to be retained by spheroplasts and the DNA's of bacteriophage fd are restricted by spheroplasts of E. coli r~ + and E. coli (v I) strains (Benzinger, 1968 ). Molholt & Fraser 0965) and Schell & Glover (1966) conclude that a surface-localized enzyme plays an essential role in the host-controlled restriction of phage/~.…”
Section: Discussionmentioning
confidence: 99%
“…The rest might be explained if the single-stranded state of DNA transferred by conjugation affords special protection to incoming DNA, but this is a difficult notion to accept. Even when single-stranded DNA is introduced directly, by transformation, it is equally as sensitive to restriction by EcoB as is double-stranded DNA (6), despite the fact that EcoB, like many other endonucleases (49,56), has little or no measurable activity towards single-stranded DNA in vitro (38).…”
Section: Discussionmentioning
confidence: 99%
“…Neither has the effect of endonuclease II on transfection been tested. The Kspecific and B-specific restriction endonucleases inactivate unmodified transfecting DNA nearly as strongly as unmodified DNA injected from viable phage (26,30,88). Finally, the weak single-strand specific endonuclease encoded by the recBC genes (131) has no detectable effect on the infectivity of circular, single-stranded 4X174 DNA (32).…”
Section: Lysozyme-edta Technique-mechanismmentioning
confidence: 99%